Strategies for Increasing the Productivity of Goat Farming Business in the Era of Industry 4.0 in Banyumas District - Krismiwati Muatip; Novie Andri Setianto; Akhmad Sodiq; Rahayu Widiyanti; Fajar Priyana (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2023)
The development of goat breeding business needs to be done so that the business can compete in the era of industrial 4.0. The study aims to formulate the strategy to increase productivity in goat breeding business on the 4.0 industry era. The study used survey methods. Determination of the sample was done using stratified random sampling that took the region based on high land, moderate and low land. Then, on each level was taken by criteria of number of goats and the dominant species. Number of sample was determined using Nomogram Harry King and the total respondents was 322 farmers. The analysis used was Causal Loop Diagram modeling and Qualitative Descriptive. The results show that to increase the productivity of goat breeders can be done with optimize Information and Communication Technology (ITC) in production factors, utilization management system application and the inovation of feed technology, optimize smartphone as promotion and trading tools, share the information via social media, supply of information service based on website or application and transformation of extension to virtual extension.